THE APPLICATION FOR LEAVE TO APPLY TO COURT FOR REVIEW OF A SCHEME OF ARRANGEMENT IN TERMS OF SECTION 115 OF THE COMPANIES ACT 71 OF 2008 Sand Grove Opportunities Master Fund Ltd v Distell Group Holdings Ltd [2022] ZAWCHC 46 - Madlela, Vela (Obiter, 2023)
Schemes of arrangement in terms of section 114 of the Companies Act 71 of 2008 (the Companies Act) have become a prevalent mechanism of implementing business combinations, takeovers or restructurings of the share capital in South Africa. In contrast to the 1973 Companies that required court approval for a company to implement a scheme of arrangement, the implementation of a scheme of arrangement under the current Companies Act is initiated by the board of directors and is subject to the supermajority rule, that is, shareholder approval by way of a special resolution. One of the principal protective mechanisms for minority shareholders in a scheme of arrangement, as in the other fundamental transactions, is the appraisal remedy in terms of section 164 of the Companies Act – which acts as an exit mechanism for dissatisfied minority shareholders instead of them thwarting the implementation of a scheme of arrangement. Another protective mechanism for dissenting shareholders is the involvement of the court in schemes of arrangement, which is, however, limited to court approval or court review of the implementation of a scheme of arrangement in clearly circumscribed circumstances. In Sand Grove Opportunities Master Fund Ltd and Others v Distell Group Holdings Ltd and Others [2022] ZAWCHC 46 (Sand Grove), the Western Cape Division of the High Court (the court) dealt with some pertinent issues relating to the application for leave to apply for court review of schemes of arrangement under section 115(3)(b), (6) and (7) of the Companies Act. These issues included the standing to bring proceedings in terms of section 115, application for leave to intervene as co-applicants in these proceedings, condonation of a non-compliance with prescribed period within which the application for leave to apply for court review must be brought, as well as the validity of the meeting and the special resolution approving the scheme of arrangement. This note, therefore, examines the above key issues raised in Sand Grove and provides a critical discussion of the judgment and its significance. The note also highlights the practical implications of this case for companies, directors, shareholders (especially dissenting minority shareholders), beneficial holders of shares and other participants under schemes of arrangement.